Lacosamide Inhibition of NaV1.7 Channels Depends on its Interaction With the Voltage Sensor Domain and the Channel Pore - Labau, Julie I. R.; Alsaloum, Matthew; Estacion, Mark; Tanaka, Brian; Dib-Hajj, Fadia B.; Lauria, Giuseppe; Smeets, Hubert J. M.; Faber, Catharina G.; Dib-Hajj, Sulayman; Waxman, Stephen G. (Frontiers in Pharmacology, 2021)
Lacosamide, developed as an anti-epileptic drug, has been used for the treatment of pain. Unlike typical anticonvulsants and local anesthetics which enhance fast-inactivation and bind within the pore of sodium channels, lacosamide enhances slow-inactivation of these channels, suggesting different binding mechanisms and mode of action. It has been reported that lacosamide’s effect on NaV1.5 is sensitive to a mutation in the local anesthetic binding site, and that it binds with slow kinetics to the fast-inactivated state of NaV1.7. We recently showed that the NaV1.7-W1538R mutation in the voltage-sensing domain 4 completely abolishes NaV1.7 inhibition by clinically-achievable concentration of lacosamide. Our molecular docking analysis suggests a role for W1538 and pore residues as high affinity binding sites for lacosamide. Aryl sulfonamide sodium channel blockers are also sensitive to substitutions of the W1538 residue but not of pore residues. To elucidate the mechanism by which lacosamide exerts its effects, we used voltage-clamp recordings and show that lacosamide requires an intact local anesthetic binding site to inhibit NaV1.7 channels. Additionally, the W1538R mutation does not abrogate local anesthetic lidocaine-induced blockade. We also show that the naturally occurring arginine in NaV1.3 (NaV1.3-R1560), which corresponds to NaV1.7-W1538R, is not sufficient to explain the resistance of NaV1.3 to clinically-relevant concentrations of lacosamide. However, the NaV1.7-W1538R mutation conferred sensitivity to the NaV1.3-selective aryl-sulfonamide blocker ICA-121431. Together, the W1538 residue and an intact local anesthetic site are required for lacosamide’s block of NaV1.7 at a clinically-achievable concentration. Moreover, the contribution of W1538 to lacosamide inhibitory effects appears to be isoform-specific.